2009
DOI: 10.1111/j.1365-2869.2008.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and time course of consolidation of visual discrimination skills in patients with narcolepsy–cataplexy

Abstract: SUMMAR Y The level of procedural skills improves in normal individuals when the acquisition is followed by a period of sleep rather than wake. If sleep plays an important role in the consolidation process the advantage it provides should be reduced or delayed when its organization is altered, as in patients with chronic sleep disorders. To test this prediction in patients with narcolepsy-cataplexy (NC), who usually have a more fragmented organization of sleep than normals, we compared the initial, intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…Consolidation of procedural memory -skill learningduring sleep has been studied using a number of tasks, including sequential finger tapping (Benedict et al, 2009;Doyon et al, 2009;Van Der Werf et al, 2009;Dresler et al, 2010;Genzel et al, 2011;Holz et al, 2012b;Wamsley et al, 2012;Antonenko et al, 2013), serial-reaction time task (Galea et al, 2010;Prehn-Kristensen et al, 2011;Ertelt et al, 2012), motor sequence task (Tucker and Fishbein, 2009;Manoach et al, 2010), mirror-tracing task (Smith et al, 2004b;Javadi et al, 2011;Puetz et al, 2011;Holz et al, 2012a), button-box sequence (Wilhelm et al, 2012), visuomotor adaptation task (Doyon et al, 2009); texture discrimination task (Gais et al, 2008;Cipolli et al, 2009), visual discrimination task (Suzuki et al, 2012), and others. These tasks usually involve fine motor skills using the fingers or hand-eye coordination, but do not typically involve balance or bodily displacements.…”
Section: Introductionmentioning
confidence: 99%
“…Consolidation of procedural memory -skill learningduring sleep has been studied using a number of tasks, including sequential finger tapping (Benedict et al, 2009;Doyon et al, 2009;Van Der Werf et al, 2009;Dresler et al, 2010;Genzel et al, 2011;Holz et al, 2012b;Wamsley et al, 2012;Antonenko et al, 2013), serial-reaction time task (Galea et al, 2010;Prehn-Kristensen et al, 2011;Ertelt et al, 2012), motor sequence task (Tucker and Fishbein, 2009;Manoach et al, 2010), mirror-tracing task (Smith et al, 2004b;Javadi et al, 2011;Puetz et al, 2011;Holz et al, 2012a), button-box sequence (Wilhelm et al, 2012), visuomotor adaptation task (Doyon et al, 2009); texture discrimination task (Gais et al, 2008;Cipolli et al, 2009), visual discrimination task (Suzuki et al, 2012), and others. These tasks usually involve fine motor skills using the fingers or hand-eye coordination, but do not typically involve balance or bodily displacements.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with primary insomnia demonstrated a lower sleep-associated memory consolidation of declarative (verbal and visual memory) memory tasks, while results are more controversial for procedural memory (depending on the test) compared to good sleepers [13]. Patients with narcolepsy show less consolidation of a visual procedural (texture discrimination) task after sleep compared to controls [14]. However, it is not known how parasomnias (including sleepwalking and REM sleep behavior disorder) affect sleep-dependent memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…Patients suffering from moderate obstructive sleep apnea (who experience frequent arousals during sleep stages N1, N2 and REM sleep and reduced brain oxygenation during sleep) demonstrated a reduced overnight improvement in procedural and verbal (but not visual) declarative memory (Kloepfer et al, 2009). Patients experiencing narcolepsy (who exhibit premature entrances into REM sleep and often exhibit difficulty in maintaining sleep continuity) displayed reduced consolidation of visual procedural memory during sleep (Cipolli et al, 2009). In patients suffering from REM sleep behaviour disorder (who experience agitated nightmares during REM sleep), we previously found that they performed overnight consolidation of a verbal declarative task (the FCSRT and the story recall test) equally well as age-matched controls, despite lower cognitive daytime performances and even concomitant Lewy body dementia in one patient (Uguccioni et al, 2013).…”
Section: Discussion General Findingsmentioning
confidence: 99%